Shifting Parenthood to Advanced Reproductive Ages: Trends, Causes and Consequences - Tomáš Sobotka (Intergenerational Justice Review)
This article discusses different aspects of the shift towards later parenthood which has affected all industrialised countries. It outlines trends in delayed childbearing and points out the increase in childlessness and growing educational disparities in first birth timing, especially among women. It reviews consequences of delayed childbearing for individuals, couples, their children and society and discusses the limited role of assisted reproduction in offsetting the age-related rise in infertility. The individual social and economic advantages of late parenthood may outweigh the biological advantage of early parenthood. In conclusion, I outline possible policy actions that may support childbearing decisions at both younger and older reproductive ages. Such policies should recognise wide heterogeneity in needs and lifestyle preferences of individuals and should not explicitly aim to encourage early parenthood.